Analysis of Facilities and Infrastructure and Solutions to Guidance and Counseling Problems in Schools - Assahrawiza; Neviyarni S; Yarmis Sukur (Journal Of Psychology, Counseling And Education, 2024)
Facilities and infrastructure at that time hampered the implementation of the teaching process or counseling guidelines. Without any infrastructure at all, the implementation of recommendation guidelines would be more difficult and the goals to be achieved would not be in accordance with expectations. Without adequate infrastructure in educational institutions, it is difficult for school counseling staff to work together in practicing school counseling. Therefore, to implement school counseling, infrastructure and facilities must be used. The purpose of this study was to determine the analysis of facilities and infrastructure and their solutions to guidance and counseling problems in schools. The method in this study is a literature review or literature review. The results of this study are the importance of guidance and counseling facilities and infrastructure, the importance of adequate facilities in organizing public services, especially in the field of education. Facilities, as goods or movable objects, and infrastructure, as basic facilities, ensure the smooth running of guidance and counseling activities in schools.